ROLE OF ARCHITECTURE IN NIGERIA'S AGRICULTURAL SECTOR - Atubi Akpomena Clinton; Adewolu Adeoye Olugbenga (Social Sciences and Education Research Review, 2025)
The demand for food in Nigeria has risen due to urbanization, especially in cities, leading to issues like food scarcity, waste, and expensive transportation. This study thoroughly examines how vertical farming could be a viable solution to these problems. Utilizing the PRISMA framework, the research reviews literature spanning from 2019 to 2024, emphasizing the advantages of vertical farming such as space utilization, higher crop production, decreased environmental harm, and water preservation. Vertical farming's capacity to function in controlled settings enables continuous production, lessening reliance on conventional supply chains susceptible to climate change, political turmoil, and economic interruptions. The results indicate that implementing vertical farming structures in cities can help address Nigeria's food security issues by enhancing local food production, cutting down on transportation-related carbon emissions, and boosting resistance to climate-related risks.